Analisis Faktor Maternal Dan Penyakit Kronik Pada Kejadian Persalinan Prematur - Eni Mustika; Fika Minata (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Preterm labor is delivery with a gestational age between 20 weeks to 37 weeks. This study aimed to determine the relationship between maternal BMI & wt gain during pregnancy, diabetes, maternal hypertension & BP, anemia, and history of infection with preterm labor. The method used was an analytic survey with a cross-sectional approach. The population in this study were all mothers who gave birth, amounting to 899 respondents, and random sampling or simple random sampling totaled 202 respondents. Data analysis was performed using univariate, bivariate, and multivariate logistic regression methods. The results of the study of 202 respondents who experienced preterm labor were 72 respondents (35.6%) and 130 respondents (64.4%) were not premature. From the statistical test results, it was found that there was a significant relationship between maternal BMI & increase in body weight during pregnancy (p-value = 0.001), hypertension & maternal BP (p-value = 0.001), anemia (p-value = 0.001) and a history of infection (p. -value = 0.040) with preterm labor and there was no significant relationship between diabetes (p-value = 0.211) and preterm labor. The conclusion is that the dominant variable with preterm labor is anemia (OR = 21.741, p-value = 0.000).